2021
DOI: 10.1097/md.0000000000024497
|View full text |Cite
|
Sign up to set email alerts
|

Three novel ATG16L1 mutations in a patient with acute myocardial infarction and coronary artery ectasia

Abstract: Introduction: Acute myocardial infarction (AMI) is a specific type of coronary artery disease (CAD) caused by the rupture of coronary atherosclerotic plaques. Coronary artery ectasia (CAE) is a rare phenotype of cardiovascular disease that may promote thrombosis and inflammatory responses leading to myocardial infarction due to abnormal dilatation of blood vessels and coronary blood flow disorders. It is a complicated disease and shows interaction between genetic and environmental factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Furthermore, three mutations (rs1816753, rs12476635, and rs2289477), the first two of which are within the gene promoter, as also found in this study, were identified in a patient with acute myocardial infarction (AMI) and coronary artery ectasia (CAE). These two mutations may promote thrombosis and inflammatory responses due to abnormal dilatation of blood vessels [44]. Additionally, other gene polymorphisms have been related to carotid atherosclerotic plaques, cancer, and susceptibility to infections [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, three mutations (rs1816753, rs12476635, and rs2289477), the first two of which are within the gene promoter, as also found in this study, were identified in a patient with acute myocardial infarction (AMI) and coronary artery ectasia (CAE). These two mutations may promote thrombosis and inflammatory responses due to abnormal dilatation of blood vessels [44]. Additionally, other gene polymorphisms have been related to carotid atherosclerotic plaques, cancer, and susceptibility to infections [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…However, as stated by Pascale et al [52], the main limitation of this study was the small sample size; therefore, the results should be interpreted with caution until further studies with larger series of patients shed more light on the importance of specific haplotypes in sporadic PD. However, case studies highlight the importance of reporting the association between haplotypes and sporadic PD [44].…”
Section: Discussionmentioning
confidence: 99%
“…According to another theory, increased nitric oxide (NO) levels can cause vasodilation and relaxation of ectatic areas [10]. Genetic factors such as angiotensin-converting enzyme DD genotype polymorphism [11], abnormal lipoprotein metabolism associated with familial hypercholesterolemia [12], potassium voltage-gated channel subfamily H member 1 (KCNH1) mutation [13], and autophagy related 16 like 1 (ATG16L1) gene mutations [14] have all been linked to CAE previously.…”
Section: Introductionmentioning
confidence: 99%